Evaluasi Penambangan Nikel Laterit Menggunakan Sistem Sidecast dalam Pembongkaran Overburden pada Bulan September 2021 di PT Paramitha Persada Tama - Lubis, Dahnil; Anarta, Rudy (Lembaga Yasin AlSys, 2026)
Overburden stripping production at PT Paramitha Persada Tama, a nickel mining company in North Konawe Regency, particularly in Pit Block C and A1B, has not reached the target of 90,000 Bcm/month, as actual production using the existing excavation–loading configuration (Excavator JCB 205, Excavator JCB 305, Excavator Sumitomo 210) and hauling equipment (Hino 500 dump trucks) was only 62,712.4 Bcm/month in September 2021. This study aimed to analyze efforts to achieve the production target by changing the overburden stripping system from sidecast to a hauling system. A comparative approach was used by examining production performance, fuel consumption, and stripping costs between the sidecast system in September 2021 and the hauling system in November 2021. Cost evaluation was conducted by calculating operator salaries and fuel consumption expenditures based on a fuel price of Rp 7,850.00/liter. The analysis showed that under the sidecast system, fuel consumption reached 51,650 liters/month with a fuel ratio of 0.8 and total expenditure of Rp 513,301,500.00, whereas the implementation of the hauling system resulted in an actual production of 97,947.41 Bcm/month with fuel consumption of 47,782 liters/month, yielding a saving of 3,868 liters/month while simultaneously achieving the production target. These findings confirm that the hauling system is more effective and efficient than the sidecast system for overburden stripping at the study site and is feasible to adopt as an operational strategy to optimize production.